Prevalence and Effect of Stroke Associated Pneumonia on in-Hospital Stay, Mortality and Functional Outcome at Discharge from Hospital - Muhammad Kazim Bashir, Afaq Naeem, Muhammad Haseeb Masood, Hira Farooq, Iqra Ijaz, Najma Fatima (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Stroke is the most prominent cause of morbidity and mortality worldwide especially in developing countries. The stroke outcome mainly related to the presence of complications and severity. Stroke associated pneumonia is the post stroke infection significantly associated with a longer hospitalization, increased risk of hospital mortality, and functional outcomes. There is scarcity of data regarding stroke associated pneumonia on a local basis in the developing countries. Therefore, present study aimed to find out the prevalence and effect of stroke associated pneumonia on in-hospital stay, mortality, and function outcome. Methodology: This observational prospective study was conducted on 500 stroke patients in the Department of Neurology and Medicine, Jinnah Hospital, Lahore from April 2021 to March 2022. Prior to study conduction, written informed consent and ethical approval was taken. All the participants were recruited for this study. Stroke was diagnosed based on relevant clinical history, brain imaging either by CT scan or MRI, and focused physical examination. Stroke patients of either gender above 18 years age with acute ischemic or hemorrhagic stroke and given written consent were included. All those patients who are already having disability due to previous stroke and other neurological or non-neurological issues were excluded from study. Baseline characteristics were recorded. SPSS version 25 was used for data analysis. Results: Of the total 500 stroke patients, there were 232 (46.4%) male and 268 (53.6%) females. The overall mean age was 62.4 ± 12.6 years. The prevalence of ischemic and hemorrhagic stroke was 334 (66.8%) and 166 (33.2%) respectively among 500 stroke patients. Hemiparesis was the most prevalent neurological findings 464 (92.8%) followed by facial palsy 432 (86.4%) and swallowing disturbance 262 (52.4%). About 186 (37.2%) stroke patients were complicated by stroke associated pneumonia. Multivariate regression analysis was used and revealed that stroke associated pneumonia could be developed in older age patients > 70 years Adjusted odd ratio AOR= 3.862 (1.21-12.86) (p=0.031) who suffered from swallowing disturbance AOR= 4.728, (2.415-9.102) (p<0.001), epileptic seizures AOR= 2.749 (1.315-5.681) (p<0.001), and moderate to severe stroke AOR= 6.183 (2.036-17.647) (p<0.001) (NIHSS=16-21). Conclusion: The present study concluded that prevalence of SAP was 37.2%. Stroke associated pneumonia is a significant medical issue or complications in stroke patients. Furthermore, older stroke patients with epileptic seizure, swallowing disturbance, and stroke severity from moderate to severe were the risk factors for increasing stroke associated pneumonia. Close monitoring and effective intervention might be needed for high risk SAP in stroke patients. Keywords: Stroke associated pneumonia, Functional outcome, Mortality, Hospital stay, Stroke